2012
DOI: 10.1093/toxsci/kfs118
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mode-of-Action Mediated by the Fetal Muscle Nicotinic Acetylcholine Receptor Resulting in Developmental Toxicity in Rats

Abstract: Sulfoxaflor (X11422208), a novel agricultural molecule, induced fetal effects (forelimb flexure, hindlimb rotation, and bent clavicle) and neonatal death in rats at high doses (≥ 400 ppm in diet); however, no such effects occurred in rabbit dietary studies despite achieving similar maternal and fetal plasma exposure levels. Mode-of-action (MoA) studies were conducted to test the hypothesis that the effects in rats had a single MoA induced by sulfoxaflor agonism on the fetal rat muscle nicotinic acetylcholine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…In order for a single MoA to be plausible, the fi ndings should have a similar incidence across dose levels from all studies. The similarity in the R 2 values between the non-linear regression analyses of the individual dose -response curves for death ( R 2 ϭ 0.93) and limb abnormalities ( R 2 ϭ 0.91), respectively, support a single MoA responsible for diff erent developmental eff ects rather than separate MoAs for each of the two major eff ects in rats (Rasoulpour et al 2012). …”
Section: Moa For Induction Of Muscle Contracture and Death In Neonatamentioning
confidence: 85%
See 4 more Smart Citations
“…In order for a single MoA to be plausible, the fi ndings should have a similar incidence across dose levels from all studies. The similarity in the R 2 values between the non-linear regression analyses of the individual dose -response curves for death ( R 2 ϭ 0.93) and limb abnormalities ( R 2 ϭ 0.91), respectively, support a single MoA responsible for diff erent developmental eff ects rather than separate MoAs for each of the two major eff ects in rats (Rasoulpour et al 2012). …”
Section: Moa For Induction Of Muscle Contracture and Death In Neonatamentioning
confidence: 85%
“…The regulatory guideline and MoA toxicity studies with sulfoxafl or described above revealed fi ndings for which an MoA had not previously been described (Rasoulpour et al 2012). In the past decade, frameworks to evaluate the MoA of adverse toxicological eff ects have been developed through the International Programme on Chemical Safety (IPCS) (Boobis et al 2006) and by the International Life Sciences Institute Risk Science Institute (Meek et al 2003).…”
Section: Dammentioning
confidence: 99%
See 3 more Smart Citations